CRIMINOLOGICAL REVIEW OF DRUG ABUSE IN THE JURISDICTION OF SALATIGA POLICE RESORT - Devian Tria Rosanti; Wenny Megawati (Universitas Labuhanbatu, 2024)
Salatiga, a small city in Indonesia with a population of 177,088, has witnessed a concerning rise in narcotics-related cases from 2019 to 2023. With 29 cases solved and 37 under investigation in 2023, this study delves into the factors driving narcotics abuse and the Salatiga Police Department's countermeasures. Employing a socio-legal approach, the study incorporates Sutherland's Differential Association Theory and Social Control Theory to gain insights. The study identifies factors such as family disharmony, socioeconomic instability, and inadequate education as contributing to narcotics abuse. The lack of social control, as emphasized by Social Control Theory, further exacerbates the situation. The Salatiga Police Department has implemented various preventive and enforcement measures, including school-based education programs, patrols in high-risk areas, and raids on entertainment venues. Addressing this issue comprehensively requires a holistic approach that integrates education, social support, and rehabilitation. The Salatiga Police Department's commitment to law enforcement and community protection through these strategies is commendable.Keywords: Law Enforcement, Narcotics Abuse, Social Control Theory